Socio-economic perspectives on consumer engagement and buying behavior - Kaufmann, Hans Rüdiger 1958-; Mohammad Fateh Ali Khan Panni 1981- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series, 2017)
"[This book] is a comprehensive reference source on new innovative dimensions of consumer behavioral studies and reveals different conceptual and theoretical frameworks. Featuring expansive coverage on a number of relevant topics and perspectives, such as green products, automotive technology, and anti-branding, this book is ideally designed for students, researchers, and professionals seeking current research on the dimensions of consumer engagement and buying behavior" - Provided by publisher